Pengaruh Pemberian Modal Kerja, Tanggung Renteng Dan Literasi Keuangan Terhadap Keberlangsungan Usaha Mikro, Kecil, dan Menengah - Siti Farida, Nikhen; Zanaria, Yulita; Padwa Sari, Gustin (Expensive: Jurnal Akuntansi dan Keuangan, 2024)
This research is a quantitative study with a quantitative descriptive method that aims to provide empirical evidence of the effect of providing working capital, joint responsibility and financial literacy on the sustainability of micro, small and medium enterprises. The population used in this study were all BTPN Syariah micro credit loan customers in Seputih Mataram District. Determination of the sample using purposive sampling method by obtaining the number of observations as many as 65 customers. Data processing in this study used SPSS version 25 calculation tools with data analysis techniques used descriptive statistics, classical assumption tests, hypothesis testing and statistical hypothesis testing. The results showed that working capital and financial literacy influenced the sustainability of micro, small and medium enterprises of BTPN Syariah customers in Seputih Mataram District, Central Lampung. Meanwhile, joint responsibility has no effect on the sustainability of micro, small and medium enterprises of BTPN Syariah customers in Seputih Mataram District, Central Lampung